2008
DOI: 10.1179/cim.2008.9.1.34
|View full text |Cite
|
Sign up to set email alerts
|

Variable long-term outcomes from cochlear implantation in children with hypoplastic auditory nerves

Abstract: This paper describes the outcomes in six children with hypoplastic cochlear nerves, demonstrated on magnetic resonance imaging who were selected for implantation because they had clear responses to sound, with hearing aids. In four of the six children the internal auditory canals were abnormally narrow; however in the remaining two the internal auditory canals were of normal width. After activation of their devices, all six children had auditory thresholds within the normal range for implanted congenitally dea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
35
0
2

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(39 citation statements)
references
References 17 publications
2
35
0
2
Order By: Relevance
“…An abnormal CVN has been reported in patients in whom the cochlear aperture size is normal or in patients with normal size IAC, or in patients with no associated cochleovestibular malformation [Glastonbury et al, 2002;Adunka et al, 2006Adunka et al, , 2007Buchman et al, 2006;Bradley et al, 2008;McClay et al, 2008;Carner et al, 2009;Warren et al, 2010;Kutz et al, 2011;Pagarkar et al, 2011;Colletti et al, 2014]. Our data highlight the association of normal cochleae, normal cochlear apertures, and normal caliber IAC with severe CVN abnormalities.…”
Section: Imaging Recommendationssupporting
confidence: 48%
See 2 more Smart Citations
“…An abnormal CVN has been reported in patients in whom the cochlear aperture size is normal or in patients with normal size IAC, or in patients with no associated cochleovestibular malformation [Glastonbury et al, 2002;Adunka et al, 2006Adunka et al, , 2007Buchman et al, 2006;Bradley et al, 2008;McClay et al, 2008;Carner et al, 2009;Warren et al, 2010;Kutz et al, 2011;Pagarkar et al, 2011;Colletti et al, 2014]. Our data highlight the association of normal cochleae, normal cochlear apertures, and normal caliber IAC with severe CVN abnormalities.…”
Section: Imaging Recommendationssupporting
confidence: 48%
“…Recent studies have reported an improvement in auditory skill development and sound awareness in children who had been diagnosed with CVN deficiency and received a CI [Casselman et al, 1997;Ito et al, 1999;Acker et al, 2001;Govaerts et al, 2003;Zanetti et al, 2006;Bradley et al, 2008;Oker et al, 2009;Kang et al, 2010;Warren et al, 2010;Buchman et al, 2011;Kutz et al, 2011;Young et al, 2012]. Clearly, some nerve fibers were available to transmit auditory signals to the brainstem [Casselman et al, 1997;Ozdoğmuş et al, 2004;Warren et al, 2010].…”
Section: Current Imaging Data Does Not Predict Auditorymentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, congenitally deaf children with OHC survival who also had structural abnormalities of the cochlear nerve rarely achieved any open set speech perception using cochlear implants even after two years of training after implant surgery (Bradley et al, 2008).…”
Section: Prediction Of the Outcome After Cochlear Implantationmentioning
confidence: 99%
“…While cochlear implantation in children has become a fairly routine procedure, there remain cases where implant candidacy decisions are difficult to make using existing evaluation procedures. Among these cases are children with cochlear nerve deficiencies (CND) (Bradley et al, 2008; Buchman et al, 2006; Govaerts et al, 2003; Walton et al, 2008; Zanetti et al, 2006). Auditory nerve abnormalities or hypoplasias may present in several forms.…”
Section: Introductionmentioning
confidence: 99%